A MEMS Electrochemical Seismometer Based on the Integrated Structure of Centrosymmetric Four Electrodes - Yumo Duan; Anxiang Zhong; Yulan Lu; Jian Chen; Deyong Chen; Junbo Wang (Micromachines, 2022)
This paper presented an electrochemical seismic micro sensor based on an integrated structure of four centrosymmetric electrodes. In this integrative structure, cathodes were not only distributed on wafer surfaces but also on the inner walls of the flow holes of the wafer, which increased the effective cathode areas and improved the sensitivity of the sensor. Numerical simulations were conducted to validate the feasibility of the integrated structure of four centrosymmetric electrodes in monitoring seismic vibrations where variations in the arrangements of the flow holes and anode width were investigated. The integrated structure of the four centrosymmetric micro electrodes was fabricated based on Micro-Electro-Mechanical Systems (MEMS) without the requirement of manual alignments. Experimental characterizations revealed that: (1) the maximum sensitivity of the electrochemical seismic sensor based on the integrated structure of four centrosymmetric electrodes was two orders of magnitude higher than that of the commercial counterpart of CME6011 and three times higher than the electrochemical seismic sensor based on the integrated structure of four planar micro electrodes; (2) the electrochemical seismic sensor based on the integrated structure of four centrosymmetric micro electrodes demonstrated comparable and even lower noise levels in comparison to CME6011. Thus, the electrochemical seismic micro sensor developed in this study may function as an enabling tool in future applications of seismic monitoring and geophysical explorations.